2022
DOI: 10.3389/fneur.2022.1006013
|View full text |Cite|
|
Sign up to set email alerts
|

Modulating swallowing-related functional connectivity and behavior via modified pharyngeal electrical stimulation: A functional near-infrared spectroscopy evidence

Abstract: IntroductionModified pharyngeal electrical stimulation (mPES) is a novel therapeutic modality for patients with neurogenic dysphagia. However, the underlying neural mechanism remains poorly understood. This study aimed to use functional near-infrared spectroscopy (fNIRS) to explore the influence of mPES on swallowing-related frequency-specific neural networks and ethology.MethodsTwenty-two healthy right-handed volunteers participated in the study. Each participant was randomly assigned to either the sham or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
0
1
Order By: Relevance
“…Our study may help to test this hypothesis. However, there are some differences between our findings and Dou's (Zhang et al, 2022(Zhang et al, , 2023. In our study, after electroacupuncture treatment of PSD patients, we found increased activation of bilateral M1 area and connectivity of M1 with the surrounding cortex; after Dou's modified pharyngeal electrical stimulation (mPES) of healthy subjects, they found a decrease in cortical activation and functional connectivity, but all participants in these studies had improved swallowing function.…”
Section: Discussioncontrasting
confidence: 79%
“…Our study may help to test this hypothesis. However, there are some differences between our findings and Dou's (Zhang et al, 2022(Zhang et al, , 2023. In our study, after electroacupuncture treatment of PSD patients, we found increased activation of bilateral M1 area and connectivity of M1 with the surrounding cortex; after Dou's modified pharyngeal electrical stimulation (mPES) of healthy subjects, they found a decrease in cortical activation and functional connectivity, but all participants in these studies had improved swallowing function.…”
Section: Discussioncontrasting
confidence: 79%